Lung CSC‐derived exosomal miR‐210‐3p contributes to a pro‐metastatic phenotype in lung cancer by targeting FGFRL1. Issue 11 (12th May 2020) - Wang, Li; He, Jun; Hu, Haoyue; Tu, Li; Sun, Zhen; Liu, Yanyang; Luo, Feng
Abstract: Lung cancer has the highest mortality rate among human cancers, and the majority of deaths can be attributed to metastatic spread. Lung cancer stem cells (CSCs) are a component of the tumour microenvironment that contributes to this process. Exosomes are small membrane vesicles secreted by all types of cells that mediate cell interactions, including cancer metastasis. Here, we show that lung CSC‐derived exosomes promote the migration and invasion of lung cancer cells, up‐regulate expression levels of N‐cadherin, vimentin, MMP‐9 and MMP‐1, and down‐regulate E‐cadherin expression. Moreover, we verified that these exosomes contribute to a pro‐metastatic phenotype in lung cancer cells via miR‐210‐3p transfer. The results of bioinformatics analysis and dual‐luciferase reporter assays further indicated that miR‐210‐3p may bind to fibroblast growth factor receptor‐like 1 (FGFRL1); silencing FGFRL1 enhanced the metastatic ability of lung cancer cells, whereas overexpressing FGFRL1 suppressed metastasis. Taken together, our results provide new insights into a potential molecular mechanism whereby lung CSC‐derived exosomal miR‐210‐3p targets FGFRL1 to promote lung cancer metastasis. FGFRL1 may be a promising therapeutic target in lung cancer.